Seven cases of Saccharomyces fungaemia related to use of probiotics. Issue 6 (30th January 2017) - Roy, Ujjwayini; Jessani, Laxman G.; Rudramurthy, Shivaprakash M.; Gopalakrishnan, Ram; Dutta, Soma; Chakravarty, Chandrashish; Jillwin, Joseph; Chakrabarti, Arunaloke
Summary: Probiotics are increasingly used in critically ill patients without enough safety data. The aim of the present study was to determine the association of probiotics with Saccharomyces cerevisiae fungaemia. Seven patients with S. cerevisiae fungaemia were reported at two hospitals in India between July 2014 and September 2015. Detailed clinical history of patients was recorded. Besides the seven patient isolates, three probiotics sachets used in those patients and five unrelated clinical isolates were used for association study by Fluorescent amplified fragment length polymorphism (FAFLP). Antifungal susceptibility testing was performed by broth microdilution technique of CLSI (M27‐A3) and interpreted according to CLSI (M27S4). Two patients were premature neonates and five were adults. They were admitted in intensive care unit and were on probiotics containing S. boulardii (except one adult patient). FAFLP analysis showed 96.4‐99.7% similarity between blood and corresponding probiotic isolates. Of the three AFLP types (group I, II, II) identified, all the probiotic isolates clustered in group I (major cluster) including majority of the blood isolates. The isolates were susceptible to all antifungal agents tested. Five patients, who could be evaluated, responded promptly to echinocandins or voriconazole. As the prescription of probiotic containing S. boulardii in critically ill patient's leads to the fungaemia, we recommend avoiding this probiotic in those patients.